INTERPRETING AND TRANSLATING OLD PRUSSIAN MICRO-TEXTS : THE TRACE OF BASEL - Ardoino, Diego (Vertimo studijos, 2017)
More than forty years after the publication of its discovery, the Trace of Basel continues to arouse great interest among the international community of Balticists and numerous contributions still appear on the topic. If the first publications generally focused almost exclusively on the linguistic aspects of the Trace of Basel, new insights based on the philological, codicological and palaeographic aspects of the micro-text have recently led to growing interest among scholars. This paper examines the relationship between the Trace of Basel and the historical context in which it appeared since this is essential in forming a plausible linguistic interpretation of the micro-text. A ‘philological’ approach is used to explore the subject. Commenting on the interpretation of the Trace of Basel given by Frederik Kortlandt, this paper will show that his assumptions are misleading and that linguistic and philological approaches are not alternative methods of analysis but part of a closely related continuum, a line of investigation along which the (correct) interpretation of the micro-text gradually takes shape. Finally, on the basis of these philological and codicological considerations, a new hypothesis on the provenance of the Trace of Basel is presented.